Successful treatment of habit cough using suggestion therapy - Sharma, Pawan; Mahapatra, Ananya; Sagar, Rajesh (Journal of Psychiatrists' Association of Nepal, 2023)
Background: Habit cough is one of the causes of chronic cough in children. Many cases do not reach the psychiatrists due to lack of specific clinical features and diagnostic tests. We present a case of 13 year old boy with habit cough who was successfully treated by suggestion therapy and lignocaine based mouth gargle as a distracter. This case highlights that suggestion therapy can be an important treatment option to this fairly common condition.